Joseph P. Laycock, New Religious Movements: The Basics, London – New York: Routledge, 2022, s. 152 - Koszałka, Łukasz (Studia Gdańskie, 2024)
Joseph P. Laycock, New Religious Movements: The Basics, Routledge: London – New York 2022, ss. 152.